The role of semen cryobanks for protecting endangered native salmonids: Advantages and perspectives as outlined by the LIFE Nat.Sal.Mo. project on Mediterranean brown trout (Molise region – Italy) - Michele Di Iorio; Giusy Rusco; Stefano Esposito; Mariasilvia D’Andrea; Alessandra Roncarati; Nicolaia Iaffaldano (Frontiers in Marine Science, 2023)
The Mediterranean brown trout is one of the most endangered freshwater species. A complicated network of climate and human influences has severely harmed its biodiversity. The introduction of alien trout is one of the most serious threats to native populations’ intraspecific diversity. In Molise region (south-Italy) an important conservation program (LIFE Nat.Sal.Mo project) has recently been proposed to preserve the genetic integrity of native Mediterranean trout. This project, alongside safeguarding and re-establishing the habitats’ usefulness aims to restore the genetic integrity of the autochthonous population. This is one of the major goals, and it is accomplished by employing frozen wild breeder semen in conjunction with proper fertilization techniques to carry out artificial reproduction to enhance genetic diversity in the progeny and maintain fitness within self-sustaining populations. In this regard, the implementation of the first European semen cryobank has played a strategic role for conserving extant genomic diversity of native population. The goal of this review is to outline the procedures developed and guidelines established for the creation of a Mediterranean trout sperm cryobank. Here, we specifically provide an overview of some of the main challenges associated with the implementation of semen cryobank, the results achieved, the prospects for restoring genetic integrity in native populations, and lastly, future views for hatchery management to preserve the wild biodiversity of native salmonid species. During the project timeframe 1,683 semen doses, from 150 native breeders were stored inside the cryobank. Our results clearly showed the efficiency of the freezing procedure used, both in vitro and in vivo. In fact, we recorded satisfactory values of post-thaw sperm motility and viability that ranged from 40% to 80%, and excellent fertilization rate in vivo, which ranged from 64% to 81%.